Dobra nowina według Deutero-Izajasza (Iz 52,7-10) - Lemański, Janusz (Verbum Vitae, 2002)
The message of Is 52,7-10 is determined by declaration made in v. 7bB: your God has begun his reign. This statement introduces reality which may be recognised and realized through peace, good and salvation, gifts offered to Gods chosen people (v. 7bA). The reason why it is possible and actually happens is because God comforts and redeems His people (v.9). The new kingship is so splendourous that even the ends of the earth can witness salvation of our Lord (v. 10b). Contents of this God Tidings is similar to what christians call Gospel of Jesus Christ (Rom 10,15). In this article the theological closeness between Is 52,7-10 and the proclamation of Jesus Christ is strongly emphasised.